Dinamika regulasi sekolah berstandar internasional di Indonesia - Qiso, Ahmad Abdul; Zuhdi, Muhammad; Abdurrahmansyah; Nafisah, Ani; Juniarni, Cittra (Ta’dibuna: Jurnal Pendidikan Islam, 2023)
This study aims to analyze the dynamics of regulation of international standard schools in Indonesia; display the implementation; and analyze its impact on Islamic educational institutions. This study uses library research methods, with historical and evaluative approaches. Information extracted by using documentation techniques. While the data analysis uses content analysis techniques. This study found: First, the dynamics of international standard school regulations began with the issuance of Perpu No. 48 of 1960, strengthened by the International Standard School (SBI) program through Permendikbud No. 78 of 2009. Then it was replaced with the SPK (Cooperation Education Unit) program regulated in Permendikbud Number 31 of 2014; Second, the regulations that have been implemented so far have shown a positive thing when viewed from the aspects of effectiveness, equity and precision. However, in the aspect of adequacy it has not been able to fully overcome the existing problems; and the responsiveness aspect has not been able to satisfy all parties; and third, the dynamics of international standard school regulation has increasingly sparked the rapid development of international standard Islamic education institutions. Abstrak Penelitian ini bertujuan menganalisis dinamika regulasi sekolah bertaraf internasional di Indonesia; mengevaluasi pelaksanaannya; dan menganalisis dampaknya terhadap lembaga pendidikan Islam. Penelitian ini menggunakan metode library research, dengan pendekatan historis dan evaluatif. Informasi digali dengan menggunakan teknik dokumentasi. Sedangkan analisis datanya menggunakan teknik content analysis. Penelitian ini menemukan: Pertama, dinamika regulasi sekolah berstandar internasional dimulai dengan lahirnya Perpu No. 48 tahun 1960, diperkuat dengan program Sekolah Berstandar Internasional (SBI) melalui Permendikbud No. 78 tahun 2009. Kemudian diganti dengan program SPK (Satuan Pendidikan Kerja sama) diatur dalam Permendikbud No. 31, tahun 2014; Kedua, regulasi yang selama ini diimplementasikan sudah menunjukkan suatu hal yang positif jika di lihat dari aspek efektivitas, pemerataan dan ketepatan. Namun, dalam aspek kecukupan belum sepenuhnya dapat mengatasi problem yang ada; dan pada aspek responsitivitas belum dapat memuaskan semua pihak; dan ketiga, dinamika regulasi sekolah bertaraf internasional semakin memantik berkembang pesatnya lembaga pendidikan Islam bertaraf Internasional.